Literature Learning to Instill Local Culture Using Digital Flipbooks for Elementary School Students - Hartati Ratna Juita; Sigit Widiyarto; N. Yeffa Afnita Apriliyani; Windi Megayanti; Aster Pujaning Ati; Bambang Sumadyo (Yayasan Keluarga Guru Mandiri, 2025)
Regional culture still feels foreign to the ears of elementary school students because students rarely receive material or content from regional culture. A one-group pretest-posttest experimental design was employed. Thirty-seven fifth-grade elementary school students participated. Data was collected through pre-and post-tests and analyzed using SPSS 24 to assess the intervention's normality, homogeneity, and effectiveness using a paired samples t-test. Folklore stories from West Java, West Sumatra, and Riau were used as learning materials. The results revealed a statistically significant difference in students' scores before and after using the digital flipbooks, indicating increased learning outcomes. Storytelling proved to be a particularly engaging method within the flipbook learning experience. Digital flipbooks are an effective tool for teaching regional literature and fostering cultural understanding among elementary school students. Digital flipbooks are interactive online publications that simulate the experience of flipping through a physical book, allowing users to view, navigate, and engage with content in a digital format. The use of storytelling within the flipbook enhanced student engagement. Schools should incorporate diverse and engaging cultural learning resources. This study contributes to the field of education by demonstrating the practical application of digital flipbooks in cultural learning and provides evidence-based support for their integration into elementary school curricula. The findings suggest that interactive multimedia resources are valuable for promoting cultural appreciation and literacy development.